Two women conversing - Unknown:::Creator::::::::::::
Photograph shows two women engaged in a conversation. They are dressed nicely and the woman on the left has a blue ribbon on her white blazer. They are in a room with many other people including what appears to be a news crew on site. The microphone and part of the camera are visible.